Arbitration in Malaysia: an overview - Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
Arbitration which is an alternative to traditional litigation is defined as ‘the determination of a matter in dispute by the judgment of one or more persons, called arbitrators, who in case of difference, usually call in an umpire to decide between them.’1 According to Mozley and Whiteley, ‘Arbitration is where two or more parties submit all matters in dispute to the judgment of arbitrators who are to decide the controversy.2 In Collins v. Collins,3 Sir John Romilly MR stated: ‘An arbitration is a reference to the decision of one or more persons either with or without an umpire, of some matter or matters in difference between the parties.’